Three empirical essays on mergers and regulation in the telecommunications industry - Seo, Daigyo (Kansas State University, 2007)
This empirical dissertation consists of three essays on mergers and regulation in the U.S. telecommunications industry. An abstract for each of the three essays follows. Essay 1: This study has attempted to measure the productivity growth associated with 25 incumbent local exchange carriers (ILECs) over the period 1996-2005 using a Malmquist productivity index. The average efficiency scores for our sample companies have not changed significantly between 1996 and 2005, which indicates that the average ILECs shows no measurable improvement in terms of optimizing their input-output combinations over time. We find some empirical evidence of a positive merger effect, although this effect diminishes over time. In addition, we find that non-merged firms underperform in terms of average productivity growth. Essay 2: This study analyzes the merger effects for 25 ILECs over the period 1996-2005 using stochastic frontier analysis with a time-varying inefficiency model. In addition, we conduct a comparison of indices between the stochastic frontier analysis and the Malmquist index method. The empirical results indicate that the sample of telecommunications firms has experienced deterioration in average productivity growth following the mergers. In addition, both approaches suggest that firms that do not merge underperform in terms of average productivity growth. Essay 3: This essay investigates whether the substitution of price cap regulation (PCR), along with other regulatory regimes, for traditional rate of return regulation (RRR) has had a measurable effect on productivity growth in the U.S. telecommunications industry. A stochastic frontier approach, which differs from previous studies, is employed to compute efficiency change, technological progress, and productivity growth for 25 LECs over the period 1988-1998. By examining the relationship between the change in productivity growth and regulatory regime variables, while controlling for other effects, we find that PCR and other regulatory regimes have a positive effect on productivity growth. However, only PCR has a significant and positive effect in both contemporaneous and lagged model specifications.
Keywords: Telecommunications; Productivity Growth; Merger; Incentive Regulation; Stochastic Frontier Analysis; Malmquist Index; Economics, General (0501)